International Diversification Gains and Home Bias in Banking - Garcia-Herrero, Alicia; Vazquez, Francisco (Washington, D.C. : International Monetary Fund, 2007)
This paper assembles a bank-level dataset covering the operations of 38 international banks from eight industrial countries and their subsidiaries overseas during 1995-2004, and studies the extent of diversification gains from their local operations abroad. The paper finds that international banks with a larger share of assets allocated to foreign subsidiaries, particularly to those located in emerging market countries, are able to attain higher risk-adjusted returns. These gains are somewhat reduced- but by no means depleted-when international banks concentrate their subsidiaries in specific geographical regions. The paper also finds a substantial home bias in the international allocation of bank assets, relative to the results of a mean-variance portfolio optimization model. Overall, international diversification gains in banking appear to be substantial, albeit largely unexploited by current bank expansion strategies. These results suggest that international diversification gains could usefully be considered in the second pillar of Basel II as the first pillar is based only on the idiosyncratic risk of recipient countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet